The Level of Pre-service Teachers’ Digital Literacy during the COVID-19 Pandemic - Asyti Febliza; Asep Kadarohman; Aulia Stephani; Zul Afdal (STAI Hubbulwathan Duri, 2023)
The COVID-19 pandemic changed the way in which things were done in schools and colleges. This study aims to find out how well pre-service teachers at a private university in Riau, Indonesia, know how to use technology based on their age, gender, and term. After two years of the COVID-19 pandemic, it was time to find out how well pre-service teachers knew how to use technology. In this study, 722 students made up the whole group. This research is a detailed quantitative study that looks into how well teachers-to-be know how to use technology. The tool is a valid and trustworthy Google form with an inquiry. Technology, Mobile/Smartphone, Social Media, Online Safety, and E-learning are the digital literacy factors that are looked into. The results of the studies show that younger pre-service teachers are better at using technology and female students are slightly better at using technology. It fits into the set group for the semester level. Study programmes were used to find out what the average level of digital literacy was. During the COVID-19 outbreak, most pre-service teachers were at an established level of digital literacy. The results of this study show that using technology for online learning during the COVID-19 pandemic makes pre-service teachers better at using technology.